GROWTH AND SURVIVAL RATE OF WESTERN WHITE PRAWNS (Litopaneaus vannamei) ON DIFFERENT SALINITY - Fadhlur Rahman; Rusliadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted for 30 days from 23 March to 22 April 2015 which was held at the Great Hall Brackishwater Aquaculture Development Jepara, Central Java Province. The aim of this research to determine the different salinity for growth and survival rate of Western white prawns (Litopenaeus vannamei). The method used is the experimental method with completely randomized design (CRD) of the factor with 3 levels a treatment. The treatment was applied, namely P1 of salinity 15 ppt, P2 of salinity 20 ppt, P3 of salinity 25 pptThe best result showed that salinity 15 ppt. Total absolute body weight, absolute body length, daily growth rate and survival rate was 2.09 grams, 6.60 cm, 0.07 grams/day and 94.7 % respectively. Water quality parameters were recorded namely a temperature is 29.1-31.6 oC, pH 7.9-8.1 and dissolved oxygen 3.84- 4.97 ppm.Keywords: Western white prawns, Salinity , Growth, Survival Rate.